A high-capacity sulfur intercalation modified negative electrode material and a preparation method thereof

By using a layered carbon substrate and concentrated sulfuric acid permeation intercalation technology, nano-sulfur is generated between the carbon substrate layers, which solves the expansion problem of the negative electrode material, achieves high capacity and stable cycle performance, and improves the electrochemical performance of the battery.

CN117577800BActive Publication Date: 2026-11-06GUANGDONG MORION NANOTECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311502517.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2026-11-06
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

Existing methods for modifying anode materials are insufficient to improve specific capacity while stabilizing battery cycle performance. Traditional coating and nanocomposite treatments suffer from expansion problems and unstable battery performance.

Method used

By combining layered stacked carbon substrates with concentrated sulfuric acid, and controlling the permeation and intercalation of the sulfur source, nano-sized elemental sulfur is generated between the carbon substrate layers. Combined with inert gas and hydrogen treatment, embedded composite modification is achieved, avoiding expansion and improving conductivity.

Benefits of technology

It achieves high specific capacity and good cycle performance without changing the size of the carbon substrate, reduces the deintercalation and expansion of the composite sulfur source, and improves the discharge specific capacity and rate performance of the anode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004544709020000071
    Figure BDA0004544709020000071
  • Figure HDA0004544709040000011
    Figure HDA0004544709040000011
Patent Text Reader

Abstract

The application discloses a high-capacity sulfur intercalation modified negative electrode material, and preparation raw materials comprise: carbon base material, concentrated sulfuric acid, deionized water and mixed gas; the mass ratio of the carbon base material and the concentrated sulfuric acid is 1:(10-50). The application adopts the combination of the layered stacked carbon base material and the concentrated sulfuric acid, the sulfur between the carbon base material layers exists in the form of nanometer size element, the existence of the intercalation sulfur improves the discharge specific capacity of the carbon base material; and does not affect the conductivity of the carbon base material, the negative electrode sheet does not exist impedance effect; in addition, in the charging and discharging process, the layered intercalation sulfur can make the carbon base material layer spacing realize micro-expansion, and improve the rate performance and cycle performance of the carbon base material. The application is an inlaid type composite modification method under the condition of not changing the size of the base material, and the limit greatly weakens the expansion phenomenon of the composite sulfur source in the deintercalation process, and greatly avoids the shuttle effect of the composite sulfur source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-capacity sulfur intercalation modified anode material and its preparation method, and specifically to the field of battery technology. Background Technology

[0002] With the development of energy storage technology, higher requirements are being placed on the energy density of secondary batteries. The key to improving battery energy density lies in increasing the specific capacity of the positive and negative electrode materials. High-specific-capacity positive electrode materials are developing rapidly, but the research and development of high-specific-capacity negative electrode materials is not yet mature. Common traditional negative electrode materials, such as carbon negative electrodes, although possessing high specific capacity after modification, suffer from severe expansion problems. The expansion during the charge-discharge deintercalation process further affects the battery's cycle performance. Existing modification methods for negative electrode materials include coating treatment or nanocomposite treatment. Coating modification reduces battery expansion, but the high specific capacity of the battery is unstable. Nanocomposite treatment can reduce the size of the substrate and reduce expansion, but it is still difficult to obtain a stable high specific capacity.

[0003] Chinese invention patent CN201510018761.4 discloses a graphite composite carbon electrode material for lead-acid batteries, the electrode it prepares, and its preparation method. It uses a multi-element epoxy resin system, with phenolic resin and lignin as curing agents. Asphalt and tar rich in multi-benzene ring structures increase conductivity after low-temperature carbonization and provide acid protection for graphite, resulting in a carbon electrode with low resistance, high mechanical strength, and resistance to sulfuric acid corrosion. However, the specific capacity of the resin-coated carbon electrode does not increase significantly. Chinese invention patent CN202310477712.1 discloses a perovskite solar cell assembled from a low-temperature carbon electrode material with embedded interface modification and its preparation method. It involves in-situ embedding heteroatom-coated carbon nanospheres into the surface of a perovskite layer for interface modification, effectively preventing moisture in the air from eroding the perovskite layer and improving the long-term stability of the device. However, the in-situ embedded nanospheres are unstable and have poor long-term cycling performance. Summary of the Invention

[0004] To improve the specific capacity, rate performance, and cycle performance of carbon anode materials, the first aspect of this invention provides a high-capacity sulfur intercalation modified anode material, the raw materials for which include: carbon substrate, concentrated sulfuric acid, deionized water, and mixed gas; wherein the mass ratio of the carbon substrate to the concentrated sulfuric acid is 1:(10-50).

[0005] In a preferred embodiment, the mass ratio of the carbon substrate to concentrated sulfuric acid is 1:(15-25).

[0006] In a preferred embodiment, the mass ratio of the carbon substrate to concentrated sulfuric acid is 1:20.

[0007] In a preferred embodiment, the carbon substrate is a layered stacked carbon substrate, which is selected from one or a combination of several of flake graphite, micro-expanded graphite, artificial graphite, and spherical graphite.

[0008] In a preferred embodiment, the particle size D of the layered stacked carbon substrate is... 50 The range is 0.5-40μm.

[0009] In a preferred embodiment, the particle size D of the layered stacked carbon substrate is... 50 It is 10-30μm.

[0010] In a preferred embodiment, the particle size D of the layered stacked carbon substrate is... 50 It is 17μm.

[0011] During the experiment, the applicant discovered that using a layered stacked carbon substrate with concentrated sulfuric acid at a weight ratio of 1:(10-50) allows for uniform intercalation of the sulfur source between the carbon substrate layers, reducing sulfur source deintercalation and electrode expansion, and improving the rate performance and cycle performance of the carbon substrate. The likely reason is that concentrated sulfuric acid, as the sulfur source, can uniformly intercalate between the layers of the stacked carbon substrate, and a weight ratio of 1:(10-50) allows for controlled intercalation. When inert gas and hydrogen sulfide mixtures are introduced in stages at low temperatures, or inert gas and hydrogen mixtures, elemental sulfur intercalation can be achieved. Since the intercalated sulfur exists between the carbon substrate layers, it does not affect the conductivity of the carbon substrate, and there is no impedance effect on the negative electrode. Furthermore, during charge and discharge, the layered structure of the intercalated sulfur allows for micro-expansion of the interlayer spacing of the carbon substrate, improving the rate performance and cycle performance of the carbon substrate.

[0012] The sulfur source in this application is intercalated between carbon substrate layers to achieve embedded composite modification without changing the substrate size. The embedded sulfur source greatly avoids the shuttle effect of the composite sulfur source and reduces the expansion phenomenon of the composite sulfur source during the deintercalation process.

[0013] In a preferred embodiment, the volume concentration of the concentrated sulfuric acid is >90%, and the mass ratio of the carbon substrate to deionized water is 1:(20-100).

[0014] In a preferred embodiment, the concentrated sulfuric acid has a volume concentration of 98%. The mass ratio of the carbon substrate to deionized water is 1:(40-80). Preferably, the mass ratio of the carbon substrate to deionized water is 1:50.

[0015] In a preferred embodiment, the mixed gas includes at least a mixture of hydrogen sulfide and an inert gas, wherein the inert gas is selected from one or more combinations of argon, nitrogen, helium, and neon.

[0016] In a preferred embodiment, the volume ratio of hydrogen sulfide to inert gas in the mixed gas is (1-5):100.

[0017] In a preferred embodiment, the mixed gas further includes a mixture of hydrogen and an inert gas.

[0018] In a preferred embodiment, the volume ratio of hydrogen to inert gas in the mixed gas is (1-5):100.

[0019] In a preferred embodiment, the volume ratio of hydrogen to inert gas or hydrogen sulfide to inert gas in the mixed gas is (1-3):100. Preferably, the volume ratio of hydrogen to inert gas or hydrogen sulfide to inert gas in the mixed gas is 1:100.

[0020] In a preferred embodiment, the inert gas is argon.

[0021] In this application, concentrated sulfuric acid can remain between the carbon substrate layers. The introduced hydrogen sulfide can react with the concentrated sulfuric acid to generate elemental sulfur, and the reaction is relatively mild. The generated elemental sulfur is single-crystal elemental nanoparticle sulfur, which can achieve uniform in-situ reaction between layers. The generated nano-elemental sulfur enables intercalation, changes the interlayer spacing, and improves the capacity of the anode material. The introduced hydrogen gas can remove residual sulfur on the surface of the carbon substrate, retain the elemental sulfur converted between layers, and maintain the stability of sulfur intercalation modification.

[0022] A second aspect of the present invention provides a method for preparing a high-capacity sulfur intercalation modified anode material, comprising the following steps:

[0023] S1. The carbon substrate is dried in an oven at 60-150℃.

[0024] S2 involves mixing dried carbon substrate with concentrated sulfuric acid and stirring at 25-60℃ for 1-10 hours to allow sulfuric acid to intercalate between carbon substrate layers.

[0025] After S3 intercalation, deionized water is added dropwise for hydrolysis. After hydrolysis, the mixture is allowed to stand to allow the carbon substrate to precipitate. The supernatant is then discarded and filtered to obtain wet material.

[0026] S4 The wet material is placed in a 70-100℃ oven and vacuum dried for 4-10 hours to obtain dry material. It is then transferred to a tube furnace, treated with mixed gas, and naturally cooled to room temperature under an argon atmosphere to obtain the negative electrode material.

[0027] In a preferred embodiment, when adding deionized water in step S3, it is necessary to guide the flow, stir, and the hydrolysis time is 0.5-2 hours, followed by a standing time of 5-24 hours.

[0028] In a preferred embodiment, the temperature in the tubular furnace in S4 is 200-500℃, and the furnace cavity pressure is ≤10. -2 Pa.

[0029] In a preferred embodiment, the temperature in the tubular furnace in S4 is 300-400℃, and the furnace pressure is 10. - 2 Pa. Preferably, the temperature in the tubular furnace in S4 is 320°C.

[0030] In a preferred embodiment, the flow rate of the mixed gas is 5-55 sccm, and the treatment time of the mixed gas is 0.5-5.5 h.

[0031] In a preferred embodiment, the steps for introducing the mixed gas are as follows: first, a mixed gas of hydrogen sulfide and argon with a flow rate of 50-55 sccm is introduced and treated for 1-5 hours, then a mixed gas of hydrogen and argon with a flow rate of 5-15 sccm is introduced and treated for 0.5-1 hours, and then the heat preservation is completed.

[0032] In a preferred embodiment, the steps for introducing the mixed gas are as follows: first, a mixed gas of hydrogen sulfide and argon with a flow rate of 50 sccm is introduced and treated for 3 hours, then a mixed gas of hydrogen and argon with a flow rate of 10 sccm is introduced and treated for 0.5 hours, and then the heat preservation is completed.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The high-capacity sulfur intercalation modified negative electrode material of the present invention adopts a combination of layered stacked carbon substrate and concentrated sulfuric acid. The sulfur in the carbon substrate layer exists in the form of nano-sized elemental substance. The presence of intercalated sulfur improves the discharge specific capacity of the carbon substrate; and does not affect the conductivity of the carbon substrate, and the negative electrode does not have an impedance effect; in addition, during the charging and discharging process, the layered structure of intercalated sulfur can realize the micro-expansion of the interlayer spacing of the carbon substrate, thereby improving the rate performance and cycle performance of the carbon substrate.

[0035] (2) The high-capacity sulfur intercalation modified negative electrode material of the present invention uses a carbon substrate and concentrated sulfuric acid in a weight ratio of 1:(10-50), which is different from the simple surface physical adsorption loading of traditional sulfur composite modification. It can realize the controllable permeation intercalation of sulfur source and realize the same-size embedded composite intercalation of sulfur in carbon substrate.

[0036] (3) The preparation method of the high-capacity sulfur intercalation modified negative electrode material of the present invention is an embedded composite modification method without changing the size of the substrate. It greatly reduces the expansion phenomenon of the composite sulfur source during the deintercalation process and greatly avoids the shuttle effect of the composite sulfur source. Attached Figure Description

[0037] Figure 1 The graph shows the cycle performance test results of the negative electrode materials prepared in Example 1 and Comparative Example 1 after they were fabricated into electrodes. Detailed Implementation

[0038] Example 1

[0039] A high-capacity sulfur intercalation modified anode material is prepared from raw materials including: carbon substrate, concentrated sulfuric acid, deionized water, and mixed gas.

[0040] The layered carbon substrate is spherical graphite prepared from high-purity natural flake graphite, and the particle size D of the spherical graphite is... 50 The size is 17μm, purchased from Qingdao Jinhui Graphite Co., Ltd. in Shandong.

[0041] The concentrated sulfuric acid has a volume concentration of 98%.

[0042] The mixed gas includes a combination of hydrogen and argon and a combination of hydrogen sulfide and argon, with a volume ratio of hydrogen to argon of 1:100 and a volume ratio of hydrogen sulfide to argon of 1:100.

[0043] A method for preparing a high-capacity sulfur intercalation modified anode material includes the following steps:

[0044] S1 The carbon substrate is dried in an oven at 100°C for 10 hours;

[0045] S2 mixes 100g of dried carbon substrate with 2kg of concentrated sulfuric acid and stirs at 35°C for 5 hours to allow sulfuric acid to intercalate between the carbon substrate layers.

[0046] After S3 intercalation, 5 kg of deionized water was added dropwise within 30 min for hydrolysis, which lasted for 1 h. After hydrolysis, the mixture was allowed to stand for 24 h to allow the carbon substrate to precipitate. The supernatant was then discarded and filtered to obtain wet material.

[0047] S4 The wet material is placed in an 80℃ oven and vacuum dried for 5 hours to obtain the dry material. It is then transferred to a tube furnace, protected by argon, and treated with a mixed gas. The material is then naturally cooled to room temperature under an argon atmosphere to obtain the anode material.

[0048] When adding deionized water in step S3, it is necessary to guide the flow and stir.

[0049] The temperature in the tubular furnace of S4 is 320℃, and the furnace chamber pressure is 10. -2 Pa.

[0050] The steps for introducing the mixed gas in S4 are as follows: under negative pressure and heat preservation conditions, a mixed gas of hydrogen sulfide and argon with a flow rate of 50 sccm is continuously introduced for 3 hours, and then a mixed gas of hydrogen and argon with a flow rate of 10 sccm is introduced for 0.5 hours, and the heat preservation is ended.

[0051] Example 2

[0052] A high-capacity sulfur intercalation modified negative electrode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that the amount of concentrated sulfuric acid added is 1.5 kg.

[0053] Example 3

[0054] A high-capacity sulfur intercalation modified negative electrode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that the amount of concentrated sulfuric acid added is 2.5 kg.

[0055] Example 4

[0056] A high-capacity sulfur intercalation modified anode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that the temperature in step S2 is 30°C.

[0057] Example 5

[0058] A high-capacity sulfur intercalation modified anode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that the temperature in step S2 is 40°C.

[0059] Example 6

[0060] A high-capacity sulfur intercalation modified anode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that in step S4, a mixed gas of hydrogen sulfide and argon with a flow rate of 50 sccm is continuously introduced for 1 hour, followed by a mixed gas of hydrogen and argon with a flow rate of 10 sccm for 0.5 hours, and then the material is kept warm.

[0061] Example 7

[0062] A high-capacity sulfur intercalation modified anode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that in step S4, a mixed gas of hydrogen sulfide and argon with a flow rate of 50 sccm is continuously introduced for 5 h, followed by a mixed gas of hydrogen and argon with a flow rate of 10 sccm for 0.5 h, and then the material is kept warm.

[0063] Example 8

[0064] A high-capacity sulfur intercalation modified anode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that the temperature in the tubular furnace in step S4 is 200°C.

[0065] Example 9

[0066] A high-capacity sulfur intercalation modified anode material and its preparation method are disclosed. The raw materials and methods are the same as in Example 1, except that the temperature in the tubular furnace in step S4 is 500℃.

[0067] Comparative Example 1

[0068] An unmodified negative electrode material, wherein the negative electrode material is the unmodified spherical graphite in Example 1.

[0069] Comparative Example 2

[0070] A negative electrode material, a sulfur / carbon negative electrode material prepared by CVD (chemical vapor deposition) evaporation nanocomposite process;

[0071] The carbon anode material is dried in an oven at 60-100℃ for 2-10 hours. Elemental sulfur and carbon anode are loaded at a mass ratio of 0.2:1 and placed in the quartz tube of a tube furnace. Elemental sulfur is loaded in a quartz boat and placed at the inlet end of the quartz tube. The carbon anode material is loaded in a flat quartz substrate and placed horizontally slightly higher than the sulfur and at the exhaust end of the quartz tube. The two are 4-15 cm apart. Elemental sulfur is in the heat preservation zone of the tube furnace, and carbon anode material is in another temperature zone (dual temperature zone).

[0072] High-purity argon gas is introduced into the quartz tube for 0.3-1 hours to purge the air from the quartz tube. The temperature of the elemental sulfur zone is raised to 200-400℃ at a heating rate of 5℃ / min, and the temperature of the carbon anode material zone is raised to 100-200℃ at a heating rate of 5℃ / min. After both zones reach the target temperature, they are held at the temperature for 0.5-2 hours. The elemental sulfur evaporates and is loaded onto the carbon anode material to obtain a nano-sulfur / carbon anode composite material.

[0073] Performance testing

[0074] The negative electrode materials of the examples and comparative examples were mixed with PVDF (polyvinylidene fluoride) and carbon black in a ratio of 98:1:1. N-methylpyrrolidone was added (just enough to completely wet the material; the amount of N-methylpyrrolidone added is not limited), and the mixture was loaded into a mixing tank and stirred in a planetary vacuum mixer to form a fine, glossy negative electrode slurry with a slurry fineness <10 μm. The slurry was coated onto copper foil to a thickness of 250 μm, baked in a 100°C forced-air oven for 6 hours, rolled, and cut into round sheets to obtain the negative electrode sheet. The negative electrode shell, gasket, negative electrode sheet, separator, lithium sheet, gasket, spring sheet, and positive electrode shell were then combined with electrolyte, pressed, and molded to obtain a coin cell. The electrical performance of the coin cell was evaluated. The test results are shown in Table 1.

[0075] Table 1

[0076]

[0077] The performance test data revealed the following: In Example 2, the amount of concentrated sulfuric acid added was too small, resulting in insufficient sulfuric acid penetration and intercalation, leading to a decrease in the electrical performance of the modified negative electrode material. In Example 3, the amount of concentrated sulfuric acid added was too large, causing the hydrolysis temperature in step S3 (adding deionized water) to be too high. This resulted in partial etching reactions between the concentrated sulfuric acid and the carbon substrate, introducing a small number of defects and causing a decrease in cycle performance. In Example 4, the intercalation temperature was low, and the Brownian motion of sulfuric acid molecules was weak, resulting in relatively slow penetration and intercalation of concentrated sulfuric acid, leading to a decrease in electrical performance. In Example 5, the intercalation temperature was high, and the Brownian motion of sulfuric acid molecules was strong, resulting in rapid penetration and intercalation of concentrated sulfuric acid. However, the relatively high intercalation temperature also caused slightly higher etching of the carbon material by the concentrated sulfuric acid, resulting in a decrease in electrical performance. The electrical performance decreased as follows: In Example 6, the hydrogen sulfide treatment time in step S4 was too short, which was not conducive to the conversion of deep intercalated sulfuric acid molecules into elemental sulfur, resulting in a decrease in electrical performance; In Example 7, the hydrogen sulfide treatment time was too long, and the converted small-sized elemental sulfur was easily lost through vaporization, leading to a decrease in sulfur doping. In addition, hydrogen sulfide is a strong reducing and corrosive gas, which has a certain etching effect on the sample, which is not conducive to the first effect, and its electrical performance was worse than that of Example 1; In Example 8, the hydrogen sulfide treatment temperature was too low, and the conversion of intercalated sulfuric acid molecules was insufficient, resulting in a decrease in electrical performance; In Example 9, the hydrogen sulfide treatment temperature was too high, and the conversion reaction of intercalated sulfuric acid molecules was violent. At the same time, the escape of the byproduct sulfur dioxide damaged the graphite structure to a certain extent, thus reducing the electrical performance.

[0078] The cyclic performance test graphs for Example 1 and Comparative Example 1 are shown below. Figure 1 .

Claims

1. A method for preparing a high-capacity sulfur intercalation modified anode material, characterized in that, Includes the following steps: S1. The carbon substrate is dried in an oven at 60-150℃. S2 involves mixing dried carbon substrate with concentrated sulfuric acid and stirring at 25-60℃ for 1-10 hours to allow sulfuric acid to intercalate between carbon substrate layers. After S3 intercalation, deionized water is added dropwise for hydrolysis. After hydrolysis, the mixture is allowed to stand to allow the carbon substrate to precipitate. The supernatant is then discarded and filtered to obtain wet material. S4. The wet material is placed in a 70-100℃ oven for vacuum drying for 4-10 hours to obtain the dry material. The dry material is then transferred to a tube furnace at a temperature of 200-500℃ and a furnace pressure of ≤10. -2 Pa, a mixed gas was introduced for treatment, and the mixture was naturally cooled to room temperature under an argon atmosphere to obtain the negative electrode material; The mixed gas includes at least a mixture of hydrogen sulfide and an inert gas, wherein the inert gas is selected from one or more combinations of argon, nitrogen, helium, and neon. The carbon substrate is a layered stacked carbon substrate.

2. The method for preparing the high-capacity sulfur intercalation modified negative electrode material according to claim 1, characterized in that, The raw materials for preparation include: carbon substrate, concentrated sulfuric acid, deionized water, and mixed gas; the mass ratio of the carbon substrate to the concentrated sulfuric acid is 1:(10-50).

3. The method for preparing the high-capacity sulfur intercalation modified anode material according to claim 1, characterized in that, The layered stacked carbon substrate is selected from one or a combination of several of flake graphite, micro-expanded graphite, artificial graphite, and spherical graphite.

4. The method for preparing the high-capacity sulfur intercalation modified anode material according to claim 3, characterized in that, The particle size D of the layered stacked carbon substrate 50 The range is 0.5-40μm.

5. The method for preparing the high-capacity sulfur intercalation modified anode material according to claim 4, characterized in that, The particle size D of the layered stacked carbon substrate 50 It is 10-30μm.

6. The method for preparing the high-capacity sulfur intercalation modified negative electrode material according to claim 1, characterized in that, The volume concentration of the concentrated sulfuric acid is >90%.

7. The method for preparing the high-capacity sulfur intercalation modified anode material according to claim 1, characterized in that, The mass ratio of the carbon substrate to deionized water is 1:(20-100).

8. The method for preparing the high-capacity sulfur intercalation modified anode material according to claim 7, characterized in that, The mass ratio of the carbon substrate to deionized water is 1:(40-80).

9. The method for preparing the high-capacity sulfur intercalation modified anode material according to claim 1, characterized in that, The volume ratio of hydrogen sulfide to inert gas in the mixed gas is (1-5):

100.

10. The method for preparing the high-capacity sulfur intercalation modified negative electrode material according to claim 1, characterized in that, When adding deionized water in S3, it is necessary to guide the flow and stir. The hydrolysis time is 0.5-2 hours, and the standing time is 5-24 hours.

11. The method for preparing the high-capacity sulfur intercalation modified negative electrode material according to claim 1, characterized in that, The flow rate of the mixed gas is 5-55 sccm, and the treatment time of the mixed gas is 0.5-3.5 h.

Citation Information

Patent Citations

  • Graphite composite carbon electrode material for lead acid battery, electrode prepared from electrode material and preparing method of electrode

    CN104681812A

  • Perovskite solar cell assembled by low-temperature carbon electrode material embedded interface modification and preparation method thereof

    CN116490047A

  • Carbon-sulfur complex, electrochemical element using the same, and lithium ion battery

    JP2013214503A